Paradoxical Embolism due to Persistent Foramen Ovale; a Case Report - Barrios, Dormar David; Roncancio, Jonathan; Avila, Albert Alejandro; Alvarado, Jaime Andrés; Montenegro, Ana Cristina (Archives of Academic Emergency Medicine, 2017)
The mean percentage of cryptogenic strokes among ischemic strokes is 31%, of which one-third may be associated with patent foramen ovale. The foramen ovale is required for blood flow through the fetal atrial septum.Â It is formed as of the fourth week of gestation, and this leads to right-left interatrial shunt that allows the passage of oxygenated blood to systemic circulation. In 75% of cases, its closure is complete by 2 years of age, but it may persist in 25% of patients. We present the case of a patient with paradoxical embolism in the lower extremities and ischemic stroke in the clinical context of a patent foramen ovale.